Pencegahan Stunting Pada Anak Dengan Posyandu di Desa Pematang Berangan Kecamatan Rambah, Kabupaten Rokan Hulu - Kusmiana Kusmiana; Beatrice Silalahi; Regina Putri; Anizar Nur Azizah; Aldifa Candra; Sohibul Adli; Rivaldo Saputra; Ella Junian Putri; Shintya Maulidya; Silvia Mayang; Mujiono Mujiono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Real Work Lecture (KKN) is a form of community service activity by students with a cross-scientific and sectoral approach at a certain time and area. The implementation of KKN activities usually lasts between one to two months and takes place in villagelevel areas. The Directorate General of Higher Education in Indonesia has requires every university to carry out KKN as an intracurricular activity that combines the tri dharma of higher education, namely: education, research, and community service. We take the theme of stunting in our service to the community in Pematang Berangan village. Stunting is a developmental disorder experienced by children due to poor nutrition, repeated infections, and inadequate psychosocial stimulation. Some of the factors that cause stunting are the practice of giving colostrum and exclusive breastfeeding, children's consumption patterns, and infectious diseases, access and availability of food ingredients as well as environmental sanitation and health.